2005
DOI: 10.1002/adfm.200400322
|View full text |Cite
|
Sign up to set email alerts
|

Biomineralized Polysaccharide Capsules for Encapsulation, Organization, and Delivery of Human Cell Types and Growth Factors

Abstract: The construction of biomimetic microenvironments with specific chemical and physical cues for the organization and modulation of a variety of cell populations is of key importance in tissue engineering. We show that a range of human cell types, including promyoblasts, chondrocytes, adipocytes, adenovirally transduced osteoprogenitors, immunoselected mesenchymal stem cells, and the osteogenic factor, rhBMP‐2 (BMP: bone morphogenic protein), can be successfully encapsulated within mineralized polysaccharide caps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 29 publications
1
83
0
Order By: Relevance
“…[22] ALG is an anionic biopolymer extracted from marine brown algae and one of the natural origin polymers with more use in tissue engineering, especially for growth factor delivery and cell encapsulation. [23] The potential of the quartz crystal microbalance with dissipation monitoring (QCM-D), as an important tool for following in situ the build-up of multilayer assemblies composed by CHI and ALG, will be investigated. Afterwards, the adsorption behavior of human serum albumin (HSA), the major protein constituent of human blood plasma, will also be assessed in real time.…”
Section: Introductionmentioning
confidence: 99%
“…[22] ALG is an anionic biopolymer extracted from marine brown algae and one of the natural origin polymers with more use in tissue engineering, especially for growth factor delivery and cell encapsulation. [23] The potential of the quartz crystal microbalance with dissipation monitoring (QCM-D), as an important tool for following in situ the build-up of multilayer assemblies composed by CHI and ALG, will be investigated. Afterwards, the adsorption behavior of human serum albumin (HSA), the major protein constituent of human blood plasma, will also be assessed in real time.…”
Section: Introductionmentioning
confidence: 99%
“…Further requirements for tissue regeneration are a supportive scaffold and alginate polysaccharide capsules offer a 3D structure for the encapsulation and organization of cells exploiting this paradigm and can not only support a range of cell skeletal cell types but allow presentation of specific stimuli to direct the formation of a desired tissue as well as allowing mechanical integrity to a cell-tissue construct (Caterson et al, 2001;Alsberg et al, 2002;, Green et al, 2005). We have used human skeletal progenitors encapsulated within alginate/chitosan polysaccharide templates to promote chondrogenesis and looked at the potential to begin to create artificial microenvironments (Pound et al, 2006(Pound et al, , 2007.…”
Section: The Chondrogenic Niche Informing Skeletal Regenerationmentioning
confidence: 99%
“…[10] Previous studies demonstrated that inorganic/organic hybrid materials [11][12][13][14] were likely to be of generic importance in the design of biocompatible microcapsules because they often exhibit complementary properties, and, in this regard, synthetic approaches based on mimicking natural processes such as biomineralization should be promising. [15][16][17] Biomineralization often involves a diffusioncontrolled deposition of inorganic minerals within porous organic polymeric matrices. Biomineralized polysaccharide capsules have potential applications for cell growth, [15,18] release of functional biomolecules, [17] gene delivery, [19] and the implications therein for tissue engineering.…”
Section: Full Papermentioning
confidence: 99%
“…[15][16][17] Biomineralization often involves a diffusioncontrolled deposition of inorganic minerals within porous organic polymeric matrices. Biomineralized polysaccharide capsules have potential applications for cell growth, [15,18] release of functional biomolecules, [17] gene delivery, [19] and the implications therein for tissue engineering. [20] For example, Green et al [15] demonstrated both in vitro and in vivo a number of human cell types and immortalized cell lines encapsulated within mineralized polysaccharide capsules, including adipocytes, chondrocytes, bone marrow cells, and mesenchymal stem cells.…”
Section: Full Papermentioning
confidence: 99%
See 1 more Smart Citation